Thermodynamic, exergo-economic and exergo-environmental analysis of hybrid geothermal-solar power plant based on ORC cycle using emergy concept (2020)
Design and optimization of the energy system with the efficient method is one the major problem in recent years. The combined emergy-exergy-economic-environmental analysis is one of new methods selected for the optimization of energy systems. At present paper, first, optimal design of thermodynamic, exergo economic and exergo environmental was developed; the geothermal power plant was used as a complement to concentrated solar power (CSP) and then combined emergy-exergy-economic-environmental analysis was conducted. A standalone geothermal cycle (first mode), as well as hybrid Geothermal-Solar cycle (second mode) were investigated to generate the heating/cooling power of the building. The close similarity of the results of the exergy and emergeeconomic analysis was very interesting. For standalone geothermal cycle, both exergo and emerge-economic analysis implied that highest value (6.02E-04 $/s and 3.1915Eþ09 sej/s) was related to turbine due to the heat generated by the impact of the blade, and the lowest value was related to ORC condenser. The exergo and emergo-economic analysis for geothermal-solar hybrid cycle, due to the increase in refrigerant pressure drop inside the coil, the evaporator (4.50E-03 $/s and 4.4699Eþ09 sej/s) and turbine (2.40E-03 $/s and 2.1920Eþ09 sej/s) had the highest amount. Also for standalone cycle, exergo and emergo-environmental implied that ORC turbine had the highest value of 1.26E-06 pts/s and 9.7201Eþ09sej/s. For hybrid geothermal-solar cycle, the evaporator (3.77E-06 pts/s and 6.1814Eþ08sej/s) and turbine (3.27E-06 pts/s and 6.37Eþ08 sej/s) had the highest amount of exergo and emergo-environmental. Solar power plants have only an initial cost and because solar energy is freely available to the system, so its economical exergy degradation is very low and has the lowest environmental exergy degradation. According to the results of the exergo-economic analysis of the hybrid power plant, the highest investment cost is related to solar power plant. It also has the lowest cost of exergy degradation because the environmental impact of fuel flow of solar panel is zero. The highest emerge-environmental rate of 3.3250Eþ09 (sej/s) was belonged to the solar power plant, but its environmental destruction rate was minimal because it does not consume fuel.